2016
DOI: 10.4274/tjo.71601
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Anterior Chamber Depth after Combined Phacovitrectomy

Abstract: Objectives:To evaluate changes in anterior chamber depth (ACD) and postoperative refractive outcomes after combined phacovitrectomy.Materials and Methods:This study included 10 eyes of 10 patients that underwent combined phacovitrectomy (study group) and 14 eyes of 14 patients that underwent phacoemulsification surgery (control group) at İstanbul Medipol University Ophthalmology Department. Preoperative and 3-month postoperative best corrected visual acuity (BCVA), ACD, change in ACD and refractive outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Mijnsbrugge et al [61] reported a more posterior position of the IOL in the phacovitrectomy group compared to single phacoemulsification group, attributed to loss of vitreous support. Gülkilik, Neudorfer and Li [62][63][64] described no significant change in ACD postoperatively in phacovitrectomy group. And Hamoudi and Huang [65,66] found an earlier position of IOL secondary to capsular fibrosis.…”
Section: Changes In Other Eye Parameters After Vitrectomymentioning
confidence: 99%
“…Mijnsbrugge et al [61] reported a more posterior position of the IOL in the phacovitrectomy group compared to single phacoemulsification group, attributed to loss of vitreous support. Gülkilik, Neudorfer and Li [62][63][64] described no significant change in ACD postoperatively in phacovitrectomy group. And Hamoudi and Huang [65,66] found an earlier position of IOL secondary to capsular fibrosis.…”
Section: Changes In Other Eye Parameters After Vitrectomymentioning
confidence: 99%